Normative tensions in filial caring for a mother with dementia: A narrative perspective. (November 2021) - Luichies, Ina; Goossensen, Anne; van der Meide, Hanneke
This article aims to gain insight in the normative struggles of adult children caring for their ageing mother living with dementia. Two Dutch autobiographical books written by siblings recording their own caregiving experience were analysed using a narrative design. Children appear to understand their normative concerns through six fields of tension. Our analysis shows that filial caregivers describe two distinct approaches to deal with these normative tensions. One approach aims to preserve the child's pre-existing personal beliefs and values, but also causes the child to demonstrate rigid and uncompromising behaviour at odds with the needs of their parent. The other approach is more reflective and flexible, prioritizing the needs of the vulnerable person over previously held values, providing an opportunity for better care. We conclude that caregiving children have to find their way between being faithful to their principles and showing moral flexibility.